PENGGUNAAN APLIKASI SMART APPS CREATOR UNTUK MENINGKATKAN KEMAMPUAN MENGENAL HURUF HIJAIYYAH PADA SISWA TUNARUNGU KELAS III DI SLB YPAC MAKASSAR - Isnataeni; Syamsuddin; Mustafa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low ability to recognize hijaiyyah letters in deaf students of grade III at SLB YPAC Makassar which is caused by the lack of use of interactive and interesting learning media for students. This study aims to determine the ability to recognize hijaiyyah letters in deaf students of grade III at SLB YPAC Makassar before using the Smart Apps Creator application, determine the ability to recognize hijaiyyah letters after using the Smart Apps Creator application, and determine the improvement in the ability to recognize hijaiyyah letters through the use of the Smart Apps Creator application. This study used a quantitative approach with descriptive research type. Data collection techniques were carried out through tests and observations. The research subject consisted of one deaf student of grade III at SLB YPAC Makassar with the initials M.A. The data were analyzed using descriptive quantitative analysis to describe the ability to recognize hijaiyyah letters before and after using the Smart Apps Creator application. The results showed that the deaf student's ability to recognize hijaiyyah letters improved after using the Smart Apps Creator application. This was indicated by the pretest score of 16.12 categorized as poor, which increased to 80 in the posttest categorized as good. Thus, the use of the Smart Apps Creator application can improve the ability to recognize hijaiyyah letters in third-grade deaf students at SLB YPAC Makassar.